Determination of Elements in Indoor Dust at Residential Buildings Nearby a Quarry Site - H. Wan Ibrahim, W; M. Ahmad Zawawi, E; Muhamad Darus, F; A. Abu Sudin, N (International Journal of Engineering and Technology, 2019)
Fifteen residence houses at different distances from a nearby limestone quarry were chosen to determine the concentration of elements in an indoor dust study. The samples were collected using a brush and a plastic dust pan. The elements concentrations were determined by wet digestion method with analysis using inductively coupled plasma–optical emission spectrometer (ICP-OES). The results show that the mean elements concentrations in residences houses were in the range 7.96 - 21.19, 0.21 – 0.83, 1.29 – 4.57, 0.14 – 0.26, 0.01 – 0.04 and 0.01 – 0.03 mgkg-1 for Ca, Mg, Fe, Ni, Pb and Zn respectively. The elements concentration in the investigated residential buildings areas were followed the order Ca > Fe > Mg > Zn > Ni > Pb. The evaluation of the elements contamination status of the indoor dust was carried out by using the geoaccumulation index (Igeo). Geoaccumulation index (Igeo) reveal that indoor dust of residential buildings was strongly polluted (Igeo > 5) with Ca, Mg and Fe.